Activity modulation and allosteric control of a scaffolded DNAzyme using a dynamic DNA nanostructure. Issue 2 (17th November 2015) - Mao, Xiuhai; Simon, Anna J.; Pei, Hao; Shi, Jiye; Li, Jiang; Huang, Qing; Plaxco, Kevin W.; Fan, Chunhai
Abstract : We report a DNA nanotechnology-enabled approach for the rational design of an allosteric deoxyribozyme by precisely and dynamically controlling the nanometer-scale interactions of two catalytic centers within a well-defined tetrahedral DNA scaffold. Abstract : Recognition of the fundamental importance of allosteric regulation in biology dates back to not long after its discovery in the 1960s. Our ability to rationally engineer this potentially useful property into normally non-allosteric catalysts, however, remains limited. In response we report a DNA nanotechnology-enabled approach for introducing allostery into catalytic nucleic acids. Specifically, we have grafted one or two copies of a peroxidase-like DNAzyme, hemin-bound G-quadruplex (hemin-G), onto a DNA tetrahedral nanostructure in such a manner as to cause them to interact, modulating their catalytic activity. We achieve allosteric regulation of these catalysts by incorporating dynamically responsive oligonucleotides that respond to specific "effector" molecules (complementary oligonucleotides or small molecules), altering the spacing between the catalytic sites and thus regulating their activity. This designable approach thus enables subtle allosteric modulation in DNAzymes that is potentially of use for nanomedicine and nanomachines.